2014
DOI: 10.1016/j.jorganchem.2014.08.025
|View full text |Cite
|
Sign up to set email alerts
|

(Spectro)electrochemical investigations on (ferrocenyl)thiophenes modified by tungsten Fischer carbenes

Abstract: A series of thiophene tungsten Fischer carbene complexes of type [(CO) 5 W=C(OMe)R] (1, R = 2-Th; 3, R = fcthFc) and [(CO) 5 W=C(OMe)-R'-(OMe)C=W(CO) 5 ] (2, R' = th; 5, R' = fcthfc) was synthesized for investigating low energy charge transfer interactions between the carbene substituents and the transition metal carbonyl fragment incorporating the thiophene heterocyclic system (Th = Thienyl; th = 2,5-thiendiyl; Fc = ferrocenyl; fc = 1,1'-ferrocenediyl).Electrochemical investigations were carried out on these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…Similar findings were made for 3 – , in combination with a vanishing of the intense MLCT absorption around 600 nm (Figure S12 in the Supporting Information). Throughout the anodic conversion of pyrazine 3 , a couple of absorption bands could be detected for 3 + in the NIR region: a high-energy NIR absorption around 9000 cm –1 , which can be attributed to a ligand to metal charge transfer (LMCT), as reported previously. ,,, …”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Similar findings were made for 3 – , in combination with a vanishing of the intense MLCT absorption around 600 nm (Figure S12 in the Supporting Information). Throughout the anodic conversion of pyrazine 3 , a couple of absorption bands could be detected for 3 + in the NIR region: a high-energy NIR absorption around 9000 cm –1 , which can be attributed to a ligand to metal charge transfer (LMCT), as reported previously. ,,, …”
Section: Resultssupporting
confidence: 73%
“…Within this context, eq is only valid for very weakly coupled (Hush) systems with Gaussian-shaped IVCT absorptions, such as that observed for 1 + . ,,, Thus, in the case of mixed-valent complexes with stronger interacting redox centers, H ab will be underestimated (vide supra). Hence, the investigation of the electronic coupling H ab is more accurate by using the transition dipole moment, which can be determined from the experimental spectra through integration of the IVCT absorption band. ,, However, the observation of a couple of NIR absorptions close together, as typical for metal-containing mixed-valent species, makes such a spectra analysis difficult (vide supra). ,,,,,, Furthermore, due to the complex capture of the effective charge transfer distance r ab , the geometrical distance of the interacting redox centers is often taken as a simplification, which is acceptable for weakly coupled systems. ,,,,, Considering all these assumptions, the presented H ab values (Table ) roughly verify the tendency of the increasing electronic interaction in the series of thiophenes 1 – 4 and in comparison with 2,5-diferrocenyl thiophene as well as 2,5-DiFcEDOT. As an alternative, the investigation of the solvatochromic behavior of IVCT absorptions in a series of mixed-valent compounds is also a useful tool to evaluate the magnitude of the electronic coupling, since the corresponding transitions lose solvent dependency with an increasing electronic coupling. ,,,, Thus, with reference to strongly coupled (class III) systems (Δν̃ max (IVCT) ≤ 100 cm –1 ), the electronic interaction in the considered mixed-valent thiophenes increases in the order 1 < 2,5-DiFcTh < 2,5-DiFcEDOT < 2 ≈ 3 < 4 to moderately coupled systems. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Similar studies were reported for bis(ferrocenylcarbene) complexes connected through a thiophene group (e.g. 522) [915]. Synthesis and electrochemical studies were also reported for several phosphine-substituted tungsten aminocarbene complexes [916].…”
Section: B Publications Focusing On Synthesis Formation or Physicasupporting
confidence: 72%
“…The overall intensities of these bands are close to what might be expected for porphyrin-centered π–π* transitions, although the presence of the lower intensity, lower energy Fe II → Ru III , Ru III → Fe III , and TPP → Fe III charge-transfer transitions cannot be excluded either. The appearance of an intervalence charge-transfer (IVCT) band in the NIR region of the electronic spectrum of [ 1 ] 2+ (Fe II –Ru III –Fe III core) can be considered a marker for the formation of the mixed-valence complex in solution . The NIR spectral transformations during the spectroelectrochemical and chemical oxidation experiments are shown in Figure and Figure S14.…”
Section: Resultsmentioning
confidence: 99%